2015
DOI: 10.3941/jrcr.v9i7.2210
|View full text |Cite
|
Sign up to set email alerts
|

Heterotaxy Polysplenia Syndrome In An Adult With Unique Vascular Anomalies: Case Report With Review Of Literature

Abstract: The pattern of anatomical organization of the thoraco-abdominal visceral and vascular structures which is not the expected normal arrangement, is called as situs ambiguous or heterotaxy syndrome. Patients with heterotaxy syndrome exhibit a wide spectrum of anatomical variations involving thoraco-abdominal structures. We present here an incidental finding of heterotaxy syndrome associated with unique vascular anomalies in a 35 year old male patient evaluated initially for nephrolithiasis by ultrasonography, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…Right isomerism is consistent with asplenia, bilateral trilobed lungs, and occasionally severe cardiovascular anomalies, whereas left isomerism is associated with polysplenia, bilateral bilobed lungs, pancreatic anomalies, and mild heart disease. [ 9 ] The cardiac anomalies in right-sided isomerism are more common and more severe than with left-sided isomerism. [ 9 ] Furthermore, the presence of cardiac lesions makes the patient susceptible to the development of congestive heart failure, so patients with right isomerism and asplenia have decreased survival compared to patients with left isomerism and polysplenia.…”
Section: Discussionmentioning
confidence: 99%
“…Right isomerism is consistent with asplenia, bilateral trilobed lungs, and occasionally severe cardiovascular anomalies, whereas left isomerism is associated with polysplenia, bilateral bilobed lungs, pancreatic anomalies, and mild heart disease. [ 9 ] The cardiac anomalies in right-sided isomerism are more common and more severe than with left-sided isomerism. [ 9 ] Furthermore, the presence of cardiac lesions makes the patient susceptible to the development of congestive heart failure, so patients with right isomerism and asplenia have decreased survival compared to patients with left isomerism and polysplenia.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the minor fissure cannot be identified in any of the follow-up radiographs and therefore the presence of a trilobed lung cannot be confirmed, although other findings are suggestive of a trilobed left lung. As for the management and treatment of this patient, taking into consideration that he has reached the age of 42 years and very few patients with situs ambiguus survive into adulthood-only 5-10% 21 of polysplenic patients without heart disease−, we can come to the conclusion that the presence of heterotaxy does not seem to have caused severe health problems throughout his life that had required medical or surgical treatment specific to this syndrome. For the same reasons, we can assume that this patient's prognosis is 'good'.…”
Section: Discussion Of the Case Reportmentioning
confidence: 99%
“…8,11 Only 5-10% of polysplenic patients without cardiac disease survive to adulthood. 21 Wang et al 22 have described the possibility of prenatal diagnosis of left and right isomerism using the correlation to some ultrasound findings. These authors make a classification based on the position of the heart that could really benefit prenatal management and follow up, therefore improving the prognosis.…”
Section: Prognosismentioning
confidence: 99%
“…Polysplenia, a recognized situs ambiguous, should be considered in cases with multiple splenic nodules on the right side of the abdominal cavity. This syndrome is associated with heterotaxia syndrome, which is defined as the occurrence of multiple splenic nodules and described as a left isomerism, or referring to the duplication of left sided structures [10], [11], [12], [13]. It has been reported that 50–90% of polysplenia syndrome cases are associated with cardiac complications [11].…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is associated with heterotaxia syndrome, which is defined as the occurrence of multiple splenic nodules and described as a left isomerism, or referring to the duplication of left sided structures [10], [11], [12], [13]. It has been reported that 50–90% of polysplenia syndrome cases are associated with cardiac complications [11]. Some degree of intestinal malrotation is also seen in approximately 70% of the patients with this syndrome, although most cases are asymptomatic [14].…”
Section: Discussionmentioning
confidence: 99%